Pembuatan Katalog Produk Digital dan Kode QR Untuk Mitra Usaha Sepatu Yaiki di Desa Karangdieng, Kabupaten Mojokerto - Dina Kamelia; Ayu Asari; Kristina Shinta P; Iefant Prasetya Nugroho (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
This community service program is designed to improve the competitiveness and marketing effectiveness of YAIKI's Shoe Business Partners, located in Karangdieng Village, Mojokerto Regency. This improvement effort is carried out through the creation of a digital product catalog integrated with QR codes as a modern promotional medium. The digital product catalog is systematically structured, interactive, and easily accessible, containing comprehensive information on the types, designs, sizes, prices, and advantages of the shoes produced. The catalog's attractive appearance is designed using design software and online platforms, thus conveying a professional impression and increasing consumer appeal. Furthermore, QR codes are created and placed on each product and promotional materials such as brochures, packaging, and posters. By scanning the QR code with a smartphone, consumers can directly connect to the digital catalog without having to manually search for information, thus making the marketing process more efficient and responsive to market needs. The program implementation method includes training in digital catalog creation using free or low-cost graphic design software and online platforms, the creation of QR codes that directly link to the catalog, and technical assistance for partners in implementing this technology into their marketing strategies. The program evaluation demonstrated increased partner understanding of digital technology, ease of product information delivery, and the potential for increased sales and broader market reach. Through this innovation, local shoe businesses in Karangdieng Village have a greater opportunity to compete in the modern market. The implementation of digital catalogs and QR codes is expected to be a practical and sustainable solution to support business growth, strengthen brand image, and encourage economic independence for the local community.